Increasing Community Capacity to Reduce Disaster Risk through the Disaster Resilient Family Program - Yuliarti, Astinana; kumalawati, Rosalina; Alif, Muhammad; Sagita, Noor Tasya; Putri, Faizah Maulidia; Rahman, Muhammad Ali; Iqbal, Muhammad (Universitas Lambung Mangkurat, 2026)
Tabing Rimbah Village in South Kalimantan is highly prone to floods and land fires, as evidenced by the 2021 floods that affected nearly its entire population. To mitigate future casualties and losses, the Disaster Resilient Family (KATANA) program was implemented to strengthen community preparedness and resilience against these recurring threats. This activity employed a Participatory Action Research (PAR) Approach, emphasizing community involvement across three stages: problem identification of existing knowledge, implementation and targeted empowerment materials, and evaluation by comparing pre- and post-test results to measure the program effectiveness. The problem identification stage was carried out in order to find out in depth how the existing conditions of the community in Tabing Rimbah village related to their understanding of the KATANA Program. This service shows significant improvement results, which are based on the paired sample T-test Pre and Post Test results. It can be concluded that there has been a substantial increase in the level of community knowledge after participating in the delivery of material compared to before in both tests conducted. Building on this statistical success, the program has generated a multi-dimensional impact: by developing 27 change agents who reached 632 households, it created a multiplier effect in disaster resilience for a community with limited educational and economic resources. Ultimately, this initiative not only establishes a foundation for the transformation into a